Charts and LMS Tables of Transfontanellar and Transvertical Ear-to-Ear Distances for Gestational Age - Arnold, Nancy; Ascherl, Rudolf Georg; Thome, Ulrich Herbert (Frontiers in Pediatrics, 2022)
Introduction: To date cranial development has only been described by analyzing occipitofrontal circumference (OFC). More precise methods of determining head measurements have not been widely adopted. The use of additional measurements has the potential to better account for the three-dimensional structure of the head. Our aim was to put forward centile curves of such measurements for gestational age along with a compound head volume index. Methods: We created generalized additive models for location, scale, and shape of two ear-to-ear distances (EED), transfontanellar (fEED) and transvertical (vEED), from birth anthropometric data. Same was done for OFC, crown-heel length, and birth weight to allow for comparison of our models with growth charts by Voigt et al. and Fenton et al. Results: Growth charts and tables of LMS parameters for fEED and vEED were derived from 6610 patients admitted to our NICU and 625 healthy term newborns. With increasing gestational age EEDs increase about half as fast compared to OFC in absolute terms, their relative growths are fairly similar. Discussion: Differences to the charts by Fenton et al. are minute. Tape measurements, such as fEED or vEED can be added to routine anthropometry at little extra costs. These charts may be helpful for following and evaluating head sizes and growth of preterm and term infants in three dimensions.